The Influence Of Competence, Training, And Career Development On Job Satisfaction And Employee Performance - Sanggar Ayu Prayoga; Minto Waluyo (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The study examined how employee performance and job satisfaction at XYZ Company are impacted by competence, training, and career development. Data are taken from the sample at this point in the data collection process. Purposive sampling is the technique employed to collect the data. In order to determine whether there is a relationship or influence between the two variables (independent variable and dependent variable), this study employs a technique. This study includes the whole population of 43 persons from XYZ company who have engaged in employee development activities in the last year. The Partials Least Squares test is used to test hypotheses. According to the findings of this study, competence has a positive and significant impact on job satisfaction, training has a positive and significant impact on job satisfaction, career development has a positive and significant impact on job satisfaction, and job satisfaction has a positive and significant impact on employee performance at XYZ company. The relationship model equation between exogenous and endogenous variables is hence Y2= 0,371 X1 + 0,202 X2 + 0,286 X3.